DEPOSITO MUDHARABAH, NPF, DAN TINGKAT BAGI HASIL TERHADAP PEMBIAYAAN BAGI HASIL PADA BUS DAN UUS DI INDONESIA TAHUN 2011-2016 - Inan Nati Ismah; Atina Shofawati (Universitas Airlangga, 2018)
The aim of the study was to determine the influence Mudharabah Deposit, NonPerforming Financing and Profit Sharing Level to Financing Based on Profit Sharing by Islamic Banks and Sharia Business Unit. This study used quantitative research, with purposive sampling. The data used for this study are secondary data gathered from Sharia Indonesia Banking Statistic on Financial Services Authority Website which is monthly report started from January 2011 till August 2016. Dependent variable in the study is financing based on profit sharing (Musyarakah and Mudharabah), then independent variable are Mudharabah Deposit, Non Performing Financing, and Profit Sharing Level. This reserach used analysis technical multiple linear regression. The regression result of this study indicate that mudharabah deposit variable, non performing financing and profit sharing level simultaneously have significant influence to financing based on profit sharing. Meanwhile non performing financing partially has significant influence to financing based on profit sharing REFERENCESAl-Qur’an dan Terjemahannya.Andraeny, Dita. 2011.